Effect of active and passive aeration on composting of household biodegradable wastes: a decentralized approach - Prashant P. Bhave; Bhargavi N. Kulkarni (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Present work aims at studying the influence of active (using external aerator) and passive (natural) aeration on composting of household biodegradable wastes. Methods To study the suitability of these reactors to household conditions, continuous loading was carried out for a period of 60 days. Both the reactors were loaded with cooked as well as raw vegetable and fruit waste. Physico-chemical parameters such as temperature, pH, C/N ratio, moisture content, total organic content, Total Kjeldahl Nitrogen and seed-germination parameters such as Germination Index (GI) and Root Length Index (RLI) of the mulch were analyzed at different stages of the composting process. Results Results confirmed that, although both types of aeration seem to have performed well under continuous loading, the maturation period required for actively aerated reactor was 37.30% lesser than that of naturally aerated reactor. Conclusion Active aeration found to be more suitable to household conditions as odor and fly nuisance was relatively less.